PENINGKATAN HASIL BELAJAR SIFAT-SIFAT PENGERJAAN HITUNG BILANGAN BULAT MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) - Napi'ah Napi'ah (Universitas Nahdlatul Ulama Blitar, 2016)
This study was conducted at the first semester at fifth grade student of SDN PURI Mojokerto in Academic Year 2013-2014. This study uses classroom action research consists of two cycles. The objects of this study as much as 23 students. The data in this study were analyzed using descriptive analysis in order to describe the teacher’s activities, the student’s activities and student’s learning outcomes in learning. The results of this study showed the average of learning outcomes in the second cycle increased from the first cycle in the amount of 84,57 with the classical completeness 73,91 %. Thus model implementaion of cooperative learning type TPS (Think Pair Share) can increase the teacher’s activities, student’s activities and learning outcomes of fifth grade students of SDN PURI Mojokerto in Academic Year 2013-2014.